The association between murine double minute 2 (MDM2) rs2279744 and endometrial cancer risk in a Chinese Han population - Wu, J-P.; Luo, X. (Cellular and Molecular Biology, 2017)
Some studies investigated the association between the murine double minute 2 (MDM2) rs2279744 polymorphism and endometrial cancer susceptibility, but provided controversial or inconclusive results. Thus, we decided to perform this case-control study to determine the association between MDM2 rs2279744 polymorphism and endometrial cancer in a Chinese Han population. A total of 215 endometrial cancer patients and 212 cancer-free controls were included in this case-control study. We genotyped the MDM2 rs2279744 polymorphism by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). GG genotype showed a statistically significantly increased risk of developing endometrial cancer (OR=1.72, 95%CI 1.08-2.76, P=0.02). Statistically significant difference was observed when the patients and controls were compared according to G versus I (OR=1.40, 95%CI 1.07-1.84, P=0.01). A significantly higher frequency of G allele was observed in patients with stage III+IV, compared to stage I+II (OR=2.24, 95%CI 1.49-3.38, P=0.001). In conclusion, the study found that MDM2 rs2279744 polymorphism was significantly associated with endometrial cancer risk in a Chinese Han population.